QOL-29. Neuropsychology for you" – tools to improve awareness of and access to neuropsychological care. (3rd June 2022) - Weiler-Wichtl, Liesa Josephine; Fohn-Erhold, Verena; Kollmann, Alina; Fries, Jonathan; Schneider, Carina; Holzer, angelika; Rosenmayr, Verena; Schreiber-Gollwitzer, Beate; Lüttich, Peggy; Ross, Henning; Pletschko, Thomas; Hopfgartner, Maximilian; et al.
Abstract: OBJECTIVE: The occurrence of neuropsychological late effects in childhood brain tumor patients is well known in literature and practice, as well as the use of neuropsychological testing and therapy procedures. Despite guidelines, actual care is quite heterogeneous and often does not meet the needs due to lack of resources. Therefore, a standardized tool to improve awareness of and access to neuropsychological assessment, but even more treatment was developed. METHODS: The core of this Quality-Improvement project is a multilevel and interdisciplinary approach characterized by iterative processes (PDSA-cycles): (1) conceptualization by interdisciplinary, multicenter teams of experts, (2) consensus in Delphi surveys by medical, nursing and psychosocial experts (N=45) and final approval by the steering group. (3) Pilot phases (N=44): Manageability and acceptance, emotional well-being and the degree of information were recorded using a process-oriented screening. RESULTS: The expert meetings resulted in two booklets ("Look closely - Psychosocial assessment" & "1, 2, 3 - All about Neuropsychology"): Each booklet offers creative methods with a high prompting character to motivate the child to participate actively in two face-to-face sessions (psychoeducational, work and exercise and reflection section). They enable patients to make themselves experts on these topics with age-appropriate, interactive methods. The Delphi survey revealed a consensus of 69%-93%. Patients using the Psychosocial-assessment booklet showed generally low negative emotions and stable positive emotions, which significantly increased during the second session (Z = 2.156, p = .031). Moreover, positive emotions increase significantly during the second session (Z = 2.805, p = .005). Self-indicated degree of information increases significantly with both booklets (Psychosocial assessment: Z = 3.133, p = .002; Neuropsychology: Z = 2.751, p = .006). CONCLUSION: The results illustrate a positive emotional approach to neuropsychological assessment and treatment. Likewise, the rapid increase in expert knowledge supports access to this specific topic and can be considered a minimum standard.